Non‐therapeutic male genital cutting and harm: Law, policy and evidence from U.K. hospitals. (4th December 2018) - Fox, Marie; Thomson, Michael; Warburton, Joshua
Abstract: Female genital cutting (FGC) is generally understood as a gendered harm, abusive cultural practice and human rights violation. By contrast, male genital cutting (MGC) is held to be minimally invasive, an expression of religious identity and a legitimate parental choice. Yet scholars increasingly problematize this dichotomy, arguing that male and female genital cutting can occasion comparable levels of harm. In 2015 this academic critique received judicial endorsement, with Sir James Munby's acknowledgement that all genital cutting can cause 'significant harm'. This article investigates the harm occasioned by MGC. It is informed by a Freedom of Information (FoI) study which provides some empirical evidence of the nature and frequency of physical harm caused by MGC in U.K. hospitals. While acknowledging the challenges and limitations of FoI research, we outline important lessons that this preliminary study contains for medical ethics, law and policy. It provides some empirical evidence to support claims regarding the risks which accompany the procedure and the obligation of health professionals to disclose them, and reveals the paucity of measures in place to ensure that harms are recorded, disclosed and monitored.